Innovative design and evaluation of medical nebulizer for preschool children: A user demand-driven approach - YanXiao Zhao; Tao Wang; Liming Zhang; Basyarah Hamat; Leah Ling Li Pang (PLoS ONE, 2025)
Aims To enhance the user experience and satisfaction of children’s medical nebulizers, and to improve adherence and the efficacy of nebulization treatments for children, this study explores an innovative design and evaluation method for children’s medical nebulizers from the perspective of user needs. Methods Firstly, this study conducts a thorough analysis of user behaviors and their potential needs for children’s medical nebulizers through field observations, User Journey Mapping (UJM), relevant user interviews, and the KJ method, thereby constructing a hierarchical model of demand indicators. Next, the Analytic Hierarchy Process (AHP) is employed to calculate the weight and priority ranking of each indicator, effectively identifying the crucial demand indicators that influence nebulizer design. Based on the findings from the demand analysis, an innovative design practice for children’s medical nebulizers is carried out. Finally, the fuzzy comprehensive evaluation (FCE) method is used to assess the user satisfaction of the proposed design scheme and an existing nebulizer product case used in children’s hospitals and compare the results to verify the feasibility and effectiveness of the design approach and scheme in this study. Conclusion The results indicate that the combined application of UJM, the KJ method, AHP, and FCE can help designers more accurately capture diverse user needs, enhance the scientific rigor and rationality of design and evaluation processes for children’s medical nebulizers, and ultimately produce products with higher user satisfaction. This study contributes to the field by providing a systematic framework for the design and evaluation of preschool-aged children’s medical nebulizers, offering theoretical guidance and practical reference for future designers.